Triggering UMTS user equipment inter-RAT cell reselection using noise jammers - Gardill, Markus; Zorn, Stefan; Weigel, Robert; Kölpin, Alexander (German Microwave Conference, 2011)
In this work a strategy for triggering an interradio access technology cell reselection in UMTS user equipment is proposed. All mobile devices within the effective range of a transmitter radiating a noise-like RF signal on the UMTS downlink frequency bands are forced to leave the UMTS cells and camp on non-UMTS cells, such as e.g., GSM. This allows to use a GSM based localization technique even in areas with UMTS coverage. In contrast to classical RF communication jammers which focus on disrupting the communication link, our exclusive goal is to trigger the inter-RAT cell reselection to GSM. In particular we estimate the necessary jammer RF power by examining the cell reselection procedure running in the user equipment (UE) and using some exemplary geographical scenarios. We use a hardware system to proof the results. Index Terms IEEE Terms 3G mobile communication , GSM , Interference , Jamming , Mobile handsets , Noise , Radio frequency INSPEC Controlled Indexing 3G mobile communication , cellular radio , jamming , radio links , radio transmitters Non Controlled Indexing GSM based localization , RF communication jammer , UMTS cell , UMTS coverage , UMTS downlink frequency band , UMTS user equipment , communication link , geographical scenario , interRAT cell reselection , interradio access technology , jammer RF power , mobile device , noise jammer , noise-like RF signal , transmitter Author Keywords UMTS , cell reselection , jammer References S. Zorn, R. Rose, A. Goetz, and R. Weigel, "A novel technique for mobile phone localization for search and rescue applications," in 2010 International Conference on Indoor Positioning and Indoor Navigation (IPIN), Sep. 2010, pp. 1-4. Abstract |Full Text: PDF (1079KB) User Equipment (UE) procedures in idle mode and procedures for cell reselection in connected mode, 3rd Generation Partnership Project Std. TS 25.304, Rev. 9.0.0, 2009. Physical layer - Measurements (FDD), 3rd Generation Partnership Project Std. TS 25.215, Rev. 9.0.0, 2009. S.-F. Su, The UMTS air-interface in RF engineering: design and operation of UMTS networks. Mcgraw-Hill Professional, 2007. ON THIS PAGE Abstract Index Terms References Brought to you by Universitatsbibliothek Erlangen Nurnberg Your institute subscribes to: IEEE/IET Electronic Library (IEL), VDE VERLAG Conference Proceedings What can I access? Terms of Use
elib2cris::1512001600,gardill2011